Analysis of Road Performance Used Indonesian Highway Capacity Manual 1997: A Case Jalan K.H Abdul Halim Majalengka-Indonesia - Purnama, Ega; Rifai, Andri Irfan; Nasrun, Nasrun (DAS Institute, 2022)
Jalan K.H Abdul Halim is one of the urban streets located in the center of Majalengka city, this road their several activity centers in Majalengka city. This area is growing so that traffic flow along this road is increasing, causing various traffic problems such as traffic jams. The development of highway construction is increasing rapidly In Indonesia, along with the rapid use of private vehicles. Road infrastructure development can be in the form of widening the shoulder of the road to minimize congestion. Data collection techniques in this study use Primary and Secondary methods. Peak currents on this road occur in the afternoon or at intervals of 17:15-17:30. Jalan K.H. Abdul Halim type is 4/2 UD or 4 Lanes 2 Directions are undivided. The capacity of Jalan K.H Abdul Halim is 1147 with DS 0,85 in the morning until noon, and 1,02 in the afternoon. The degree of saturation on this road is obtained, namely Sunday morning and Sunday afternoon 0.85, while on Sunday afternoon, it reaches 1.02. The results showed that LoS in the morning and afternoon was C and changed to F in the afternoon. LoS with an F value in the afternoon is quite surprising because a city with a large population is experiencing extraordinary traffic jams.